Enhancing Value For Money Performance In Local Government Organizations: The Role Of Public Financial Accountability And Internal Control - Bambang Jatmiko; Berliana Sofia Haya; Tiyas Puji Utami (Jurnal Reviu Akuntansi dan Keuangan, 2022)
This study examines the role of public financial accountability and internal control implementation on the performance of value for money of Local Government Organizations (LGOs). This study also investigates the role of internal control on public financial accountability and the intervening role of public financial accountability. This study was conducted at the Yogyakarta City Government from October 1 to November 15, 2021, using a survey method. Questionnaire responses obtained were 121, coming from 30 LGOs. The partial least square (PLS) technique was then employed to test the hypotheses. The results revealed that the public financial accountability and internal control implementation were directly associated with the value for money performance of LGOs. Additionally, the internal control implementation was positively associated with public financial accountability, while the public financial accountability played a role as a partial intervening variable (p-value = 0.012). It was also found that the variable with the greatest significant effect on value for money performance was an internal control (p-value = 0.00). The results of this study provide critical practical implications to be considered by local governments to improve their value for money performance through strengthening accounting policy aspects.